# Toán Lớp 6: ( x – 1/2 ) + ( x – 1/6 )+ ( x – 1/12 ) + ( x – 1/20 ) + – + ( x – 1/90 ) + ( x – 1/110 ) = 12/11

Toán Lớp 6: ( x – 1/2 ) + ( x – 1/6 )+ ( x – 1/12 ) + ( x – 1/20 ) + …. + ( x – 1/90 ) + ( x – 1/110 ) = 12/11

### 0 bình luận về “Toán Lớp 6: ( x – 1/2 ) + ( x – 1/6 )+ ( x – 1/12 ) + ( x – 1/20 ) + – + ( x – 1/90 ) + ( x – 1/110 ) = 12/11”

1. (x – 1/2) + (x – 1/6) + (x – 1/12) + … + (x – 1/110) = 12/11
=> (x + x + … + x) – (1/2 + 1/6 + 1/12 + … + 1/110) = 12/11
Ta có:
1/2 + 1/6 + 1/12 + … + 1/110
= 1/(1.2) + 1/(2.3) + 1/(3.4) + … + 1/(10.11)
= 1 – 1/2 + 1/2 – 1/3 + .. + 1/10 – 1/11
= 1 – 1/11
= 10/11
Do đó:
(x + x + … + x) – (1/2 + 1/6 + 1/12 + … + 1/110) = 12/11
=> 10x – 10/11 = 12/11
=> 10x = 12/11 + 10/11
=> 10x = 22/11
=> x = 1/5
Vậy x = 1/5

2. Giải đáp+Lời giải và giải thích chi tiết:
(x -1/2) + ( x – 1/6 )+ ( x – 1/12 ) + ( x – 1/20 ) + …. + ( x – 1/90 ) + ( x – 1/110 ) = 12/11
=> (x + x + … + x) – (1/2 + 1/6 + 1/12 + … + 1/110) = 12/11
Ta có: 1/2 + 1/6 + 1/12 + … + 1/110
=> = 1/(1.2) + 1/(2.3) + 1/(3.4) + … + 1/(10.11)
=> = 1 – 1/2 + 1/2 – 1/3 + .. + 1/10 – 1/11
=> = 1 – 1/11
=> 10/11
Lại có: (x + x + … + x) – (1/2 + 1/6 + 1/12 + … + 1/110) = 12/11
=> 10x – 10/11 = 12/11
=> 10x = 22/11
=> x =1/5
Vậy x= 1/5
$@Pipimm~$